The nuclear receptor : factsbook - Laudet, Vincent (Factsbook series., 2002)
The FactsBook Series has established itself as the best source of easily accessible and accurate facts about protein groups. They use an easy-to-follow format and are researched and compiled by experts in the field. This Factsbook is devoted to nuclear receptors. The first section presents an introduction and describes the mode of action of the receptors in general. The second section of the book contains detailed entries covering each type of receptor. Entries provide information on: Nomenclature and structure Isolation DNA binding properties Ligands Expression Target genes Knockouts Disease association Gene structure, promoter and isoforms Chromosomal location Amino acid sequences Key references.